Survey on blockchain-based applications in internet of vehicles. (June 2020) - Mendiboure, Leo; Chalouf, Mohamed Aymen; Krief, Francine
Abstract: Vehicular networks are evolving towards a new paradigm, the Internet of Vehicles (IoV). With IoV, vehicles should be able to communicate with their environment using heterogeneous access technologies. To make it reality, security, privacy, cooperation and trust establishment in vehicular networks should be considered. Blockchain, a popular distributed ledger technology, could be a way to overcome these challenges. That is why the integration of this technology within vehicular networks is currently under study. The aim of this survey is to provide directions for future work in the area of Blockchain-based vehicular networks. To do so, existing research works aiming to overcome vehicular challenges using the Blockchain technology are presented and compared. Moreover, different requirements related to the deployment of Blockchain-based applications in vehicular networks are identified and analysed. Finally, challenges related to the integration of the Blockchain technology within vehicular networks are discussed.